Review of Company 6, Company 7, Red Bird (Trevor Wishart), Beach Singularity and Menagerie (Trevor Wishart), The Solo Trumpet 1966-76 (John Wallace with Lysis), Dualyses (Lysis), Awakenings (Tim Wheater), Descriptive Improvisations (Dave Maddison), From S - Bracefield, Hilary (Contact: A Journal for Contemporary Music (1971-1990), 1981)